2018
DOI: 10.3389/fphys.2018.01060
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling Protein 2 in Cardiovascular Health and Disease

Abstract: Uncoupling protein 2 (UCP2) belongs to the family of mitochondrial anion carrier proteins. It uncouples oxygen consumption from ATP synthesis. UCP2 is ubiquitously expressed in most cell types to reduce oxidative stress. It is tightly regulated at the transcriptional, translational, and post-translational levels. UCP2 in the cardiovascular system is being increasingly recognized as an important molecule to defend against various stress signals such as oxidative stress in the pathology of vascular dysfunction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 130 publications
(140 reference statements)
4
52
1
Order By: Relevance
“…UCP2 has also been reported to regulate oxidative stress in other diseases. For instance, UCP2 deficiency promotes oxidative stress in cardiovascular diseases [33]. Likewise, in our study, the knock-down of UCP2 suppressed the effects of Klotho on H 2 O 2 -induced oxidative stress and apoptosis in PDLSCs.…”
Section: Discussionsupporting
confidence: 72%
“…UCP2 has also been reported to regulate oxidative stress in other diseases. For instance, UCP2 deficiency promotes oxidative stress in cardiovascular diseases [33]. Likewise, in our study, the knock-down of UCP2 suppressed the effects of Klotho on H 2 O 2 -induced oxidative stress and apoptosis in PDLSCs.…”
Section: Discussionsupporting
confidence: 72%
“…Uncoupling proteins (UCPs) are present in the inner mitochondrial membrane and allow the entry of protons into the mitochondrial matrix, resulting in both the generation of heat and attenuation of oxidant production (23,24). To determine whether the increased proton leak observed in older adults was due to upregulation of UCPs, we measured the protein abundance of UCP2.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
“…The association between UCPs and hypertension was discovered in lab studies [29,30], and was verified in Asian population [31,32]. Molecular epidemiology studies found UCP2 polymorphism alters the risk of developing CAD in some populations [33,34], while the relation between UCPs and obesity was widely recognized in several populations [35][36][37].…”
Section: Discussionmentioning
confidence: 89%